Abducted by a Terrestrial Alien: Sensory Distortions, Weird Fungi and Aerial Anomalies in a Decrepit Mountain Cabin - Hakonen, Aki (Anthropology of consciousness, 2026)
This account explores how circumstances verging on the other-worldly alter human perception and consciousness in a fieldwork situation. The case study involves an archaeological field survey team stranded for a time on a remote Lapland mountain. By applying the method of weirding, drawing inspiration from the narrative force of weird fiction, we examine how the team interacted with their decrepit shelter - a cabin teeming with fungal life amidst the terrestrial alien entity of the mountain. The experimental paper applies reflexive, autoethnographic writing in conceptualizing the experience of the unusual circumstances, considering what such otherworldly episodes can reveal about human engagement with the unfamiliar.